Penerapan E-Library dan Pelatihan Pemanfaatan Media Pembelajaran Digital di SMKN 3 Sukawati - Luh Made Yulyantari; I Gusti Ngurah Wikranta Arsa; I Nyoman Rudy Hendrawan; Ni Ketut Dewi Ari Jayanti; Gde Sastrawangsa; Ni Made Dewi Kansa Putri (Journal of Community Development, 2024)
SMKN 3 Sukawati is one of the State Vocational High Schools (SMK) in Gianyar Regency, Bali. The lessons given are adjusted to the SMK major taken. SMKN 3 Sukawati has competent teaching staff in their fields of study so that it is qualified and becomes one of the best SMK in Gianyar Regency. The SMKN 3 Sukawati library is good but has not been managed digitally, because IT staff have not specifically handled the library and the need for library staff to be trained in library management using information technology. In addition, the results of the interview found that teachers needed to improve their digital skills in terms of developing digital teaching materials. The solution offered is the implementation of an e-library in the form of installing a web-based library system, training in the use of the Web-Based Library System and training in the use of learning media using the Canva Application. The achievements of the community service outputs are in the form of installing a library system on the school's internal network, understanding of library staff regarding the function of the library system, and increasing teachers' knowledge of the use of digital learning media by 50% based on a comparison between pretest and posttest scores. Other outputs are in the form of appropriate technology and training modules.